(untitled) (Research, Society and Development, 2020)
Consumption is an essential factor for the whole of society, as it is through it that there is the generation of income, jobs and contribution to the country’s economy. Considering this scenario, companies started to invest in means that increase their sales, being able to choose to make their products available online, which provide practicality and convenience, and are often used by young people. Therefore, this study seeks to identify the online shopping behavior of young students at a University of Rio Grande Do Sul. A quantitative survey was carried out under three aspects: student purchasing habits, student purchasing habits via internet and your personal characterization. For this, a questionnaire was applied to a non-probabilistic sample. In addition, a theoretical basis was carried out regarding e-commerce, logistics, young consumer behavior and the factors that influence the purchase decision. Regarding the final considerations, it was found that the reason why students usually buy over the internet is due to the existing promotions, together with the lower value, when compared to physical stores, in addition to valuing the convenience, which is seen as one of the fundamental characteristics of e-commerce, also seek information about products in order to verify their reliability.